Sources of information-seeking on sexually transmitted infections and safer sex by older heterosexual Australian men and women - Lyons, A.; Mikolajczak, G.; Heywood, W.; Fileborn, B.; Minichiello, V.; Hinchliff, S.; Malta, S.; Dow, B.; Barrett, C.; Brown, Graham (2018)
© 2018 Taylor & Francis. Sexually transmitted infections (STIs) have risen among older people in Australia and other countries. To guide future initiatives, we examined sources of information that older people use or are willing to use for knowledge about safer sex and STIs, including whether there are any gender differences. A total of 2137 Australian adults aged 60+ years completed a nationwide survey. Analyses focused on participants who were at risk of an STI (n = 686; 220 women and 466 men). Overall, information-seeking on STIs in the last year was low (18% men; 15% women). When sought, common sources included general media outlets (e.g., magazines, TV), healthcare providers (HCPs), and the Internet. HCPs were the most relied upon source among both women and men. Brochures, websites, and HCPs were rated highest as future sources; however, women indicated they were more willing than men to have information provided by brochures and websites. STI information-seeking was generally low, but there was willingness among both men and women to use a range of sources for gaining future information.